A Nonessential African Swine Fever Virus Gene UK Is a Significant Virulence Determinant in Domestic Swine - Zsak, L. (American Society for Microbiology, 1998)
Sequence analysis of the right variable genomic region of the pathogenic African swine fever virus (ASFV) isolate E70 revealed a novel gene, UK, that is immediately upstream from the previously described ASFV virulence-associated gene NL-S (L. Zsak, Z. Lu, G. F. Kutish, J. G. Neilan, and D. L. Rock, J. Virol. 70:8865–8871, 1996). UK, transcriptionally oriented toward the right end of the genome, predicts a protein of 96 amino acids with a molecular mass of 10.7 kDa. Searches of genetic databases did not find significant similarity between UK and other known genes. Sequence analysis of the UK genes from several pathogenic ASFVs from Europe, the Caribbean, and Africa demonstrated that this gene was highly conserved among diverse pathogenic isolates, including those from both tick and pig sources. Polyclonal antibodies raised against the UK protein specifically precipitated a 15-kDa protein from ASFV-infected macrophage cell cultures as early as 2 h postinfection. A recombinant UK gene deletion mutant, ΔUK, and its revertant, UK-R, were constructed from the E70 isolate to study gene function. Although deletion of UK did not affect the growth characteristics of the virus in macrophage cell cultures, ΔUK exhibited reduced virulence in infected pigs. While mortality among parental E70- or UK-R-infected animals was 100%, all ΔUK-infected pigs survived infection. Fever responses were comparable in E70-, UK-R-, and ΔUK-infected groups; however, ΔUK-infected animals exhibited significant, 100- to 1,000-fold, reductions in viremia titers. These data indicate that the highly conserved UK gene of ASFV, while being nonessential for growth in macrophages in vitro, is an important viral virulence determinant for domestic pigs.